Education Program in Astronomy for the Community in Banjar City: Increasing Interest and Understanding of Science - Pribadi, Pandu; Rusliana, Iu; Nurohman, Arip (Universitas Ahmad Dahlan, 2024)
The educational program integrating falak science with astronomy is designed to increase interest and understanding of science among students in Banjar City. Through interactive and practical approaches, this program aims to develop students' analytical and scientific skills. The program's implementation involves a series of workshops including direct celestial observations using telescopes and computer simulations, as well as group discussions. Evaluation, conducted using pre-test and post-test questionnaires and open discussions, shows a significant increase in students' understanding and interest in Falak science and astronomy. The average understanding score increased by 22 points (44%), and the interest in further study increased by 40%. This program not only provides academic benefits but also equips students with practical skills and a broader understanding of the world around them.